Geochemical Weathering of Volcanic Materials at Southern Catena of Mount Merapi - Aini, Lis Noer; Hanudin, Eko (Faculty of Geography, Universitas Gadjah Mada, 2025)
Soil fertility is enhanced by eruptions of Mount Merapi, which deposits pyroclastic debris rich in weatherable primary minerals. Therefore, this study aimed to assess the geochemical weathering index of soils in the southern catena of Mount Merapi, an area affected by the 2010 eruption. Soil samples were collected to describe 4 geomorphic units, namely the higher, middle, lower, and foot slopes. X-ray fluorescence (X-RF) was conducted to determine total element content, and five weathering indexes (Weathering Index of Parker (WIP), Vogt's Residual Index (V), Chemical Index of Alteration (CIA), Chemical Index of Weathering (CIW), and Plagioclase Index of Alteration (PIA)) were calculated. The results show that aluminum (Al) was the most abundant oxide, followed by calcium (Ca), potassium (K), magnesium (Mg), and sodium (Na). Weathering indexes suggested moderate weathering (WIP > 100, V > 1) with a significant presence of fresh volcanic material (CIA, CIW, PIA between 50-100, closer to 50). Variations in each horizon signified the vertical and horizontal movement of mobile elements. The C horizon (deeper layer) had a higher WIP but lower values for the other indexes. In conclusion, geomorphological units influenced the distribution of fresh volcanic material, weathering products, and translocation of elements. Weathering index values reflected the ongoing release of nutrients from minerals. This information was crucial for developing nutrient management strategies in the Merapi region.Received: 2024-04-26 Revised: 2024-06-21 Accepted: 2025-02-19 Published: 2025-02-25